Characterization of physiological parameters in soybean with genetic improvement in seed yield - Keep, Nathan R. (Kansas State University, 2013)
Recent results from a genetic gain study have illustrated the contribution of plant breeding to the improvement in seed yield of soybean (Glycine max (L.) Merr.). The objective of this research was to characterize the changes in several physiological parameters that have occurred in the released cultivars with improvement of seed yield. Sixty maturity group III and 54 maturity group IV cultivars, released from the 1920's through 2010, were evaluated in dryland and irrigated environments at Manhattan, KS in 2010 and 2011. Genotypes were planted in four-row plots, 3.4 m long, spaced 76 cm apart, arranged in a randomized complete block design with four replications. Genotypes were evaluated for canopy temperature, leaf chlorophyll content, pollen germination, leaf chlorophyll fluorescence, leaf antioxidants, and yield components. Canopy temperature measurements were captured between 1000h and 1400h using an infrared camera multiple times from R1 continuing through R6. Leaf chlorophyll content was measured using a SPAD meter several times from R1 through R6. In vitro pollen germination was measured using incubation temperatures of 28 and 34° C, beginning at late R1 through the end of flowering. Leaf chlorophyll fluorescence was measured beginning at R1 through R6. Leaf antioxidants were analyzed for total antioxidant capacity and electrolyte leakage by collecting leaves from the top 3rd to 5th trifoliate at R4 and R6. Yield components were analyzed from a hand harvested 0.33 m section of one border row. Genotypes differed significantly for canopy temperature, leaf chlorophyll content, pollen germination, and yield components. No significant differences were found for leaf chlorophyll fluorescence or leaf antioxidants. Seed yield increased with year of release. Canopy temperature was negatively correlated and leaf chlorophyll content was positively correlated with year of release in both maturity groups. No significant correlation with year of release was found for in vitro pollen germination or electrolyte leakage. Leaf chlorophyll fluorescence, yield components, and total antioxidant capacity was positively correlated in the maturity group IV genotypes with year of release. Evaluation of these parameters may serve as a basis to select for seed yield, or to assess the abiotic stress tolerance of a genotype.
Keywords: Soybean; Physiological parameters; Seed yield; Canopoy Temperature; Agronomy (0285)